2016
DOI: 10.17140/aftnsoj-2-131
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residue Dissipation Upon Storage and Processing in Chickpea Legume for Food Safety

Abstract: Aim: Pesticide residue dissipation in chickpea legume under simulated storage conditions as well as effect of processing techniques was investigated. Further, the impact of pesticide residues was studied on micronutrient bioavailability. Background: Food quality and safety have assumed an important dimension in current scenario. It is important to investigate the pesticide residues present in the grains from storage in warehouses and their dissipation through processing. Methods: Pesticide residues in chickpea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Chlorpyrifos was highly degraded in pressure cooking and microwave cooking (Kaushik et al, 2016). DDT and its metabolites were decreased in the range of 15.6 to 58.8%, while malathion, chlorpyrifos, pp ‐DDT and lindane were reduced by 51.9, 44.7, 29.8, and 73% in milk pasteurization at 65°C for 30 min (Abou‐Arab, 1999b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chlorpyrifos was highly degraded in pressure cooking and microwave cooking (Kaushik et al, 2016). DDT and its metabolites were decreased in the range of 15.6 to 58.8%, while malathion, chlorpyrifos, pp ‐DDT and lindane were reduced by 51.9, 44.7, 29.8, and 73% in milk pasteurization at 65°C for 30 min (Abou‐Arab, 1999b).…”
Section: Resultsmentioning
confidence: 99%
“…DDT and its derivative residues had a greater reduction on pressure cooking at 3 min for 15 psi with microwave cooking for 6 min in green beans (Kaushik et al, 2016). Spinach on cooking at 122°C for 66 min resulted for reduces 100% reduction of azinphos‐methyl, 96% of malathion, and 100% of methyl parathion and also cooking of tomato at 100°C for 30 min showed 71–81.6% dissipation of selected OP's (Abou‐Arab, 1999a; Kaushik et al, 2016). The above studies revealed that applying for heat and pressure in the pressure cooking process can modify the cottonseed and pesticide component interaction through increases in volatilization and degradation, thus resulted in reduced residue deposition in the end products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooking has been documented to reduce the aged pesticide residues in the foods (Chavarri et al, 2005). Kaushik et al (2016) reported the significant lowering of deltamethrin residues in chick pea after subjecting to cooking. Other moist thermal cooking treatments (steaming, blanching, and pasteurization) also contributes to significant pesticide content decrease (Keikotlhaile et al, 2011;Bajwa et al, 2014).…”
Section: Effective Household Treatmentsmentioning
confidence: 99%